HAM dan Hukum Humaniter Internasional: Analisis Konflik Israel dan Palestina - Indriani, Susi; Desiandri, Yati Sharfina (Politica: Jurnal Hukum Tata Negara dan Politik Islam, 2024)
The long-running conflict between Israel and Palestine has yet to find a bright light. The international community became aware of this situation and denounced Israel's actions in Palestine. Various parties believe that Israel has committed grave human rights breaches, while many Israeli supporters argue that the attack is a form of vengeance and protection for Israel against attacks by Palestinian supporters. The purpose of this study is to examine the Israeli-Palestinian conflict from the standpoint of international humanitarian law and human rights. Primary, secondary, and tertiary legal resources are the sources of legal materials employed in the normative juridical research process. This study employs a conceptual and case-based approach, methodologies for collecting legal materials through library studies, and analysis of legal materials through the use of legal materials obtained to address problems. The research findings revealed that Israel has violated humanitarian norms (humanity). There were multiple cases in which the Israeli military breached humanitarian precepts. The use of heavy weaponry with uncertain consequences caused significant damage, and several Palestinians died. The Palestinian people's situation is deteriorating due to a food supply problem. Until recently, the International Court of Justice (ICC) has taken no action to prosecute war crimes committed by Zionist Israel.